2022
DOI: 10.3389/fcimb.2021.813520
|View full text |Cite
|
Sign up to set email alerts
|

Sialidase Activity in the Cervicovaginal Fluid Is Associated With Changes in Bacterial Components of Lactobacillus-Deprived Microbiota

Abstract: IntroductionSialidase activity in the cervicovaginal fluid (CVF) is associated with microscopic findings of bacterial vaginosis (BV). Sequencing of bacterial 16S rRNA gene in vaginal samples has revealed that the majority of microscopic BV cases fit into vaginal community-state type IV (CST IV), which was recently named “molecular-BV.” Bacterial vaginosis-associated bacterial species, such as Gardnerella spp., may act as sources of CVF sialidases. These hydrolases lead to impairment of local immunity and enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…are associated with both bacterial vaginosis 108,109 and intra-amniotic infection [110][111][112] . They are key producers of the enzyme sialidase, which can degrade the mucosa of the vaginal epithelium, resulting in tissue damage 108, 109,113,114 . The genus Sneathia has two species, S. sanguinegens and S. vaginalis (formerly S. amnii 115 ).…”
Section: Discussionmentioning
confidence: 99%
“…are associated with both bacterial vaginosis 108,109 and intra-amniotic infection [110][111][112] . They are key producers of the enzyme sialidase, which can degrade the mucosa of the vaginal epithelium, resulting in tissue damage 108, 109,113,114 . The genus Sneathia has two species, S. sanguinegens and S. vaginalis (formerly S. amnii 115 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ferreira et al . observed that many BV-related taxa (especially belonging to Prevotella genera) were enriched in sialidase-positive vaginal samples and that only two taxa, including Lactobacillus helveticus , were associated with sialidase-negative samples [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these species, Gardnerella vaginalis (GV) is thought to play a key role in the pathogenesis of BV [ 5 ]. Indeed, GV can produce various virulence factors—including sialidase, a hydrolase able to degrade local immunoglobulin A (IgA) and vaginal mucins, likely contributing to the diminished viscosity of local secretion, resulting in an increased vulnerability to pathogens [ 6 , 7 ]. Moreover, GV has a great ability to form a biofilm acting as a scaffold to which other anaerobic species, such as Atopobium vaginae and Prevotella spp., can subsequently attach [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have isolated and identified 9 genomospecies of Gardnerella through cpn60 gene typing, whole genome sequencing and other methods ( Schellenberg et al., 2016 ; Schellenberg et al., 2017 ; Hill and Albert, 2019 ; Vaneechoutte et al., 2019 ; Qin and Xiao, 2022 ). Many investigations have focused on identifying the differences in the ability to adhere to vaginal epithelial cells, virulence and drug resistance among genomospecies and the relevance of the distribution of Gardnerella genomospecies with the occurrence, symptoms or clinical outcome of BV, but the results lack consistency ( Santiago et al., 2011 ; Onderdonk et al., 2016 ; Hardy et al., 2017 ; Hilbert et al., 2017 ; Deng et al., 2018 ; Janulaitiene et al., 2018 ; Ferreira et al., 2021 ; Khan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%